Proceedings of the Fourth ACM International Conference on Web Search and Data Mining 2011
DOI: 10.1145/1935826.1935875
|View full text |Cite
|
Sign up to set email alerts
|

Identifying task-based sessions in search engine query logs

Abstract: The research challenge addressed in this paper is to devise e↵ective techniques for identifying task-based sessions, i.e. sets of possibly non contiguous queries issued by the user of a Web Search Engine for carrying out a given task. In order to evaluate and compare di↵erent approaches, we built, by means of a manual labeling process, a ground-truth where the queries of a given query log have been grouped in tasks. Our analysis of this ground-truth shows that users tend to perform more than one task at the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
135
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 103 publications
(137 citation statements)
references
References 26 publications
(28 reference statements)
1
135
1
Order By: Relevance
“…In a previous work [Lucchese et al 2011], we already proved that user tasks can effectively be found by exploiting the lexical and semantic content similarity of queries issued by individuals within specific search contexts (i.e., time-bounded subsessions of the original query session). Conversely, the same approach would not be able to discover collective tasks if applied directly to users' queries, because queries that are issued by two users, which are lexically or semantically similar, might refer to different latent needs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work [Lucchese et al 2011], we already proved that user tasks can effectively be found by exploiting the lexical and semantic content similarity of queries issued by individuals within specific search contexts (i.e., time-bounded subsessions of the original query session). Conversely, the same approach would not be able to discover collective tasks if applied directly to users' queries, because queries that are issued by two users, which are lexically or semantically similar, might refer to different latent needs.…”
Section: Introductionmentioning
confidence: 99%
“…In Lucchese et al [2011], we already showed that users perform multitasking search activities in the query streams issued to a search engine . Multitasking refers to the way users interact with a search engine, by intertwining different tasks within the same time period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also use many of the same lexical features: Jaccard coefficient, tri-gram character overlap, and Levenshtein distance. We borrow a feature presented by Lucchese et al [4], which computes the semantic similarity between two queries by the cosine similarity between vectors of tf-idf scores over Wikipedia documents. We also use their weighted connected components clustering method once the pair-wise classifications have been made.…”
Section: Extended Abstractmentioning
confidence: 99%
“…Previous studies have observed an average of 2.6-3.3 queries per search task [2,3,4] and Jones and Klinkner [2] found 16% of tasks were revisited over a three-day span of Yahoo! logs.…”
mentioning
confidence: 99%